Money creation in a neoclassical economy: Equilibrium multiplicity and the liquidity trap - Lukas Altermatt; Hugo van Buggenum; Lukas Voellmy (ETH Zurich, KOF Swiss Economic Institute, 2024)
We introduce banks that issue liquid deposits backed by bonds and capital into an otherwise standard cash-in-advance economy. Liquidity transformation by banks increases aggregate consumption and investment relative to a cash-only economy but can also lead to inefficient overinvestment. Furthermore, liquidity transformation can lead to multiple steady-state equilibria with different interest rates and real outcomes. Whenever multiple equilibria exist, one of them constitutes a 'liquidity trap', in which nominal bond rates equal zero and banks are indifferent between holding bonds and reserves. Whether economic activity is higher in a liquidity trap or in a (coexisting) equilibrium with positive interest rates is ambiguous, but the liquidity trap equilibrium is more likely to go in hand with overinvestment.
Keywords: E4; E5; 330; Banks; Liquidity; Monetary Policy; Zero-Lower Bound